2023
DOI: 10.1021/acs.orglett.3c00139
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Catalyzed Coupling of Alkenes and Enones: Sakurai–Michael-type Conjugate Addition of Catalytic Allyliron Nucleophiles

Abstract: The iron-catalyzed coupling of alkenes and enones through allylic C(sp 3 )−H functionalization is reported. This redoxneutral process employs a cyclopentadienyliron(II) dicarbonyl catalyst and simple alkene substrates to generate catalytic allyliron intermediates for 1,4-addition to chalcones and other conjugated enones. The use of 2,4,6-collidine as the base and a combination of triisopropylsilyl triflate and LiNTf 2 as Lewis acids was found to facilitate this transformation under mild, functional group-toler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
(17 reference statements)
1
6
0
Order By: Relevance
“…Soon after, iron-catalyzed coupling of olefines 51 and enones 52 through allylic C(sp 3 )À H functionalization by cyclopentadienyliron(II) dicarbonyl catalyst was reported (Scheme 26). [66] Similarly to the previous reports, the [Cp*Fe(CO) 2 (thf)] + [BF 4 ] À catalyst is able to coordinate and enhance the CÀ H acidity of allyl benzene derivatives 51. Then, a pyridine base (collidine) can be used for the abstraction of the α-proton to deliver a nucleophilic allyliron intermediate.…”
Section: Cà H Activation Of Unsaturated Compoundssupporting
confidence: 55%
See 1 more Smart Citation
“…Soon after, iron-catalyzed coupling of olefines 51 and enones 52 through allylic C(sp 3 )À H functionalization by cyclopentadienyliron(II) dicarbonyl catalyst was reported (Scheme 26). [66] Similarly to the previous reports, the [Cp*Fe(CO) 2 (thf)] + [BF 4 ] À catalyst is able to coordinate and enhance the CÀ H acidity of allyl benzene derivatives 51. Then, a pyridine base (collidine) can be used for the abstraction of the α-proton to deliver a nucleophilic allyliron intermediate.…”
Section: Cà H Activation Of Unsaturated Compoundssupporting
confidence: 55%
“…Soon after, iron‐catalyzed coupling of olefines 51 and enones 52 through allylic C(sp 3 )−H functionalization by cyclopentadienyliron(II) dicarbonyl catalyst was reported (Scheme 26). [66] …”
Section: C−h Activation Of Unsaturated Compoundsmentioning
confidence: 99%
“…Instead, we turned to silyl triflates as strong Lewis acids that irreversibly trap the incipient enolate ion intermediates as silyl enol ethers, which could be cleaved in a subsequent workup step to reveal the β-phthalimido ketone. 36 We posited that this initial trapping as the silyl enol ether could also prevent the occurrence of deamination as a side reaction. In preliminary experiments, we found that an acidic workup (in contrast to fluoride-mediated or base-mediated desilylation) led to good yields of the ketone and minimal formation of the deaminated product.…”
Section: Resultsmentioning
confidence: 99%
“…29–35 We further discovered that these nucleophilic organoiron species will undergo electrophilic functionalization with chalcone derivatives through a 1,4-addition process. 36…”
Section: Introductionmentioning
confidence: 99%
“…Michael addition, a nucleophilic addition of β-carbon, is one of the most efficient methods in organic synthesis for producing C–C and C–X (X = O, N, or S) bonds (1,4-addition reaction). It is noted to be an important contender for producing an enantioselective Michael adduct in organocatalytic asymmetric synthesis 103–105 (Scheme 28).…”
Section: Reactions Of Chalcone Derivativesmentioning
confidence: 99%